Nature of T cell epitopes in lupus antigens and HLA-DR determines autoantibody initiation and diversification. Issue 3 (25th September 2018) - Zhao, Zhenhuan; Ren, Jiling; Dai, Chao; Kannapell, Carol C; Wang, Hongyang; Gaskin, Felicia; Fu, Shu Man
Abstract : Objectives: The generation of systemic lupus erythematosus (SLE)-related autoantibodies have been shown to be T cell dependent and antigen driven with HLA-DR restriction. In this study, the initiating antigen(s) and the mechanism of autoantibody diversification were investigated. Methods: T cell epitopes (T-epitopes) of SmD1 (SmD) were mapped by T-T hybridomas generated from DR3 + AE 0 mice immunised with SmD and with SmD overlapping peptides. TCRs from the reactive hybridomas were sequenced. The core epitopes were determined. Bacterial mimics were identified by bioinformatics. Sera from DR3 + AE 0 mice immunised with SmD peptides and their mimics were analysed for their reactivity by ELISA and immunohistochemistry. Samples of blood donors were analysed for HLA-DR and autoantibody specificities. Results: Multiple HLA-DR3 restricted T-epitopes within SmD were identified. Many T-T hybridomas reacted with more than one epitope. Some of them were cross-reactive with other snRNP peptides and with proteins in the Ro60/La/Ro52 complex. The reactive hybridomas used unique TCRs. Multiple T-epitope mimics were identified in commensal and environmental bacteria. Certain bacterial mimics shared both T and B cell epitopes with the related SmD peptide. Bacterial mimics induced autoantibodies to lupus-related antigens and to different tissues. HLA-DR3 + blood donors made significantly more SLE-related autoantibodies. Conclusions: The unique antigenic structures of the lupus-related autoantigens provide the basis for being targeted and for T and B cell epitope spreading and autoantibody diversification with unique patterns. SLE-related autoantibodies are likely generated from responses to commensal and/or environmental microbes due to incomplete negative selection for autoreactive T cells. The production of SLE-related antibodies is inevitable in normal individuals. The findings in this investigation have significant implications in autoimmunity in general.